Effects of Dietary Energy Concentration and Feed Intake on Growth Performance of Newly Received Growing Cattle Fed Diets Based on Corn and Corn Co-Products - Colton D. Weir; Zachary M. Duncan; William R. Hollenbeck; Sean P. Montgomery; Tyler J. Spore; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:This study’s focus was to evaluate if feeding equal amounts of energy from a high-energy limit-fed diet has an effect on growth performance of growing beef cattle when compared to traditional high-roughagead libitumdiets. Study Description:A total of 392 crossbred heifers were fed one of four experimental diets for a 70-day receiving period. Treatments included a high-roughage diet formulated to provide 45 Mcal of net energy for gain (NEg) per 100 lb of dry matter (DM) and fed forad libitumintake (AL) or a high-energy diet formulated to provide 60 Mcal of NEgper 100 lb of DM and fed at 75% (LIM-75), 80% (LIM-80), or 85% (LIM-85) ofad libitumintake. Treatments were designed to equalize for energy intake between calves assigned to AL and LIM-75. The Bottom Line:Restricting feed intake while maintaining energy intake does not negatively influence growth performance of newly received growing beef cattle. In times of high forage cost or shortened growing periods producers could program gains based on their own financial and personal needs.
Keywords: limit-feeding; growing cattle; restricted intake